Share my life : a journey of love, faith and redemption - Kem; Ritz, David (Simon & Schuster, 2023)
Kem goes back to the very beginning to introduce his grandmother who worked as a sharecropper in the South and had thirteen children. As Kem's family rises from the sharecropping and ultimately lands in Detroit, there is an unspoken mantra of "hard things are better left unsaid," which has devastating consequences down the line. His mother is never without a beer in her hand, and his relationship with his father is oddly tense. Emotionally starved, Kem internalizes harmful feelings, eventually spiraling to drug use in his search for relief. At nineteen, Kem is homeless, roaming the cold Detroit streets. In the overly bright AA halls, Kem comes across men like himself verbalizing their feelings. The meetings help him discover his own voice, using music as an outlet that has since touched millions.